Characteristics of high-intensity interval training influence anthropometrics, glycemic control, and cardiorespiratory fitness in type 2 diabetes mellitus: a systematic review and meta-analysis of randomized controlled trials - Opazo-Díaz, E.; Montes-de-Oca-García, A.; Galán-Mercant, A.; Marín-Galindo, A.; Corral-Pérez, J.; Ponce-González, J. G. (Sports Medicine, 2024)
Background: Exercise is a non-pharmacological intervention for type 2 diabetes mellitus (T2DM), including moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT). Despite diverse exercise protocol variations, the impact of these variations in HIIT on T2DM anthropometrics, glycemic control, and cardiorespiratory fitness (CRF) remains unclear. Objective: The aim was to examine the influence of HIIT protocol characteristics on anthropometrics, glycemic control, and CRF in T2DM patients and compare it to control (without exercise) and MICT. Methods: This review is registered in PROSPERO (CRD42021281398) and follows Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search, employing "high-intensity interval training" and "diabetes mellitus" in PubMed and Web of Science databases, with a "randomized controlled trial" filter, spanned articles up to January 2023. Results: Of 190 records, 29 trials were included, categorized by HIIT interval duration, training volume, and intervention period. Long-duration, high-volume, and long-term HIIT yields superior outcomes compared to control conditions for body mass, waist circumference, fasting plasma glucose, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), glycosylated hemoglobin (%HbA1c), and CRF. The findings favored HIIT over MICT for body mass in long-duration, high-volume, and short-term intervals (mean difference [MD] - 3.45, - 3.13, and - 5.42, respectively, all p < 0.05) and for CRF in long and medium work intervals and high volume (MD 1.91, 2.55, and 2.43, respectively, all p < 0.05), as well as in medium and long-term intervention (MD 2.66 and 2.21, respectively, all p < 0.05). Regardless of specific HIIT characteristics, no differences were found in the HIIT versus MICT comparison for glycemic control. Conclusions: Specific HIIT protocol characteristics influence changes in anthropometrics, glycemic control, and CRF compared to control groups. However, compared to MICT, only longer duration, higher volume, and short-term HIIT improved body mass, waist circumference, and CRF in individuals with T2DM.